A Study on the Implementation of Electric Vehicles as Technical Service Fleet at PT. PLN (Persero) - Ayyub Rifkhi Harisma; A.A.B. Dinariyana (Dinasti Publisher, 2025)
Indonesia is making the shift from fossil fuel-powered vehicles to electric vehicles due to technological advancements and the increasing demand for cleaner energy. Through Presidential Instruction No. 7 of 2022 concerning the Use of Battery Electric Vehicles as Operational and/or Official Vehicles for Central and Regional Government Institutions, the Indonesian government has taken action to hasten the adoption of battery electric vehicles. Similar difficulties are faced by PT. PLN (Persero), Indonesia's primary electricity supplier. Using electric vehicles as technical service vehicles is one calculated move that can be made. However, a thorough analysis is required to evaluate a number of factors, such as technical limitations, expenses, and suitable vehicle selection, prior to widespread deployment. The purpose of this study is to assess how PT. PLN (Persero) might use electric vehicles as technical service vehicles. In this study, the Analytical Hierarchy Process (AHP) and the Preference Ranking Organization Method for Enrichment Evaluation (PROMETHEE) were combined to rank electric vehicle alternatives according to operational, technical, and financial criteria. Failure Mode and Effect Analysis (FMEA) was also used to identify potential failures and preventive measures. The findings indicate that FMEA can suggest a number of vehicle options based on the minimal requirements obtained from the Risk Priority Number (RPN) analysis. These specifications can then be used as a foundation for the creation of supporting electric vehicle charging station infrastructure and procurement tenders. Furthermore, Electric Vehicle A1 is the best choice for PLN's technical service fleet, according to the combination of AHP and PROMETHEE. By using these three strategies, the risk of failure is reduced, operational effectiveness is guaranteed, and the clean energy transition is supported in accordance with national policies and corporate goals.